Constitutive Expression of the Immunosuppressive Tryptophan Dioxygenase TDO2 in Glioblastoma Is Driven by the Transcription Factor C/EBPβ - Kudo, Takumi; Prentzell, Mirja T.; Mohapatra, Soumya R.; Sahm, Felix; Zhao, Zhongliang; Grummt, Ingrid; Wick, Wolfgang; Opitz, Christiane A.; Platten, Michael; Green, Edward W. (Frontiers in Immunology, 2020)
Catabolism of the essential amino acid tryptophan is a key metabolic pathway contributing to the immunosuppressive tumor microenvironment, and therefore a viable drug target for cancer immunotherapy. In addition to the rate-limiting enzyme indoleamine-2,3-dioxygenase (IDO1), tryptophan catabolism via tryptophan-2,3-dioxygenase (TDO2) is a feature of many tumors, particularly malignant gliomas. The pathways regulating TDO2 in tumors are poorly understood; using unbiased promoter and gene expression analyses we identify a distinct CCAAT/enhancer-binding protein β (C/EBPβ) binding site in the promoter of TDO2 essential for driving constitutive TDO2 expression in glioblastoma cells. Using TCGA data we find that C/EBPB expression is correlated with TDO2, and both are enriched in malignant glioma of the mesenchymal subtype and associated with poor patient outcome. We determine that TDO2 expression is sustained mainly by liver-enriched inhibitory protein (LIP) isoform of C/EBPβ and interleukin-1β, which activates TDO2 via C/EBPβ in a mitogen-activated protein (MAP) kinase-dependent fashion. In summary, we provide evidence for a novel regulatory and therapeutically targetable pathway of immunosuppressive tryptophan degradation in a subtype of glioblastoma with a particularly poor prognosis.